Clinical manifestations of severe enterovirus 71 infection and early assessment in a Southern China population. Issue 1 (December 2017) - Yang, Si-da; Li, Pei-qing; Li, Yi-min; Li, Wei; Lai, Wen-ying; Zhu, Cui-ping; Tao, Jian-ping; Deng, Li; Liu, Hong-sheng; Ma, Wen-cheng; Lu, Jia-ming; Hong, Yan; et al.
Abstract Background Enterovirus 71 (EV-A71) shows a potential of rapid death, but the natural history of the infection is poorly known. This study aimed to examine the natural history of EV-A71 infection. Methods This was a prospective longitudinal observational study performed between January 1st and October 31st, 2012, at three hospitals in Guangdong, China. Subjects with positive EV-A71 RNA laboratory test results were included. Disease progression was documented with MRI, autopsies, and follow-up. Symptoms/signs with potential association with risk of death were analyzed. Results Among the 288 patients, neurologic symptoms and signs were observed (emotional movement disorders, dyskinesia, involuntary movements, autonomic dysfunction, and disturbance of consciousness). Some of them occurred as initial symptoms. Myoclonic jerks/tremors were observed among >50% of the patients; nearly 40% of patients presented fatigue and 25% were with vomiting. Twenty-eight patients (9.7%) presented poor peripheral perfusion within 53.4 ± 26.1 h; 23 patients (8.0%) presented pulmonary edema and/or hemorrhage within 62.9 ± 28.6 h. Seventeen (5.9%) patients were in a coma. Seven (2.4%) patients died within 62.9 ± 28.6 h. Seventy-seven survivors underwent head and spinal cord MRI and 37.7% (29/77) showed abnormalities. Two fatal cases showed neuronal necrosis, softening, perivascular cuffing, colloid, and neuronophagia phenomenon in the brainstem. Conclusions Patients with EV-A71 infection showed high complexity of symptoms and onset timing. Death risk may be indicated by autokinetic eyeball, eyeball ataxia, severe coma, respiratory rhythm abnormality, absent pharyngeal reflex, ultrahyperpyrexia, excessive tachycardia, pulmonary edema and/or hemorrhage, and refractory shock and ataxic respiration. Early assessment of these symptoms/signs is important for proper management.